Positional information resolves structural variations and uncovers an evolutionarily divergent genetic locus in accessions of Arabidopsis thaliana. - Lai, A.; Denton-Giles, Matthew; Mueller-Roeber, B.; SChippers, J.; Dijkwel, P.; Dijkwel, P. (Oxford University Press, 2011)
Genome sequencing of closely related individuals has yielded valuable insights that link genome evolution to phenotypic variations. However, advancement in sequencing technology has also led to an escalation in the number of poor quality–drafted genomes assembled based on reference genomes that can have highly divergent or haplotypic regions. The self-fertilizing nature of Arabidopsis thaliana poses an advantage to sequencing projects because its genome is mostly homozygous. To determine the accuracy of an Arabidopsis drafted genome in less conserved regions, we performed a resequencing experiment on a 3 ~71-kb genomic interval in the Landsberg erecta (Ler-0) accession. We identified novel structural variations (SVs) between Ler-0 and the reference accession Col-0 using a long-range polymerase chain reaction approach to generate an Illumina data set that has positional information, that is, a data set with reads that map to a known location. Positional information is important for accurate genome assembly and the resolution of SVs particularly in highly duplicated or repetitive regions. Sixty-one regions with misassembly signatures were identified from the Ler-0 draft, suggesting the presence of novel SVs that are not represented in the draft sequence. Sixty of those were resolved by iterative mapping using our data set. Fifteen large indels (>100 bp) identified from this study were found to be located either within protein-coding regions or upstream regulatory regions, suggesting the formation of novel alleles or altered regulation of existing genes in Ler-0. We propose future genome-sequencing experiments to follow a clone-based approach that incorporates positional information to ultimately reveal haplotype-specific differences between accessions.